Стан культурно-рекреаційної сфери та соціального здоров’я в оцінках населення України та жителів міста Луцька - Семченко, Юлія Олександрівна; Семченко, Юлия Александровна; Semchenko, Yuliia O.; Тимчук, Тетяна Олегівна; Тымчук, Татьяна Олеговна; Tymchuk, Tetiana O. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Політична та соціально-економічна кризи, військові дії на Донбасі спричинили негативну динаміку щодо достатності благ культурно-рекреаційної сфери, зокрема після 2014 р. Так, лучани відчули нестачу можливості повноцінно проводити дозвілля (45,8 %; 19,2 %; 28,1 %); відпочивати (54,8 %; 35,8 %; 42,9 %); медичної допомоги (40,5 %; 44,6 %; 45,9 %); здоров’я (36,5 %; 22,2 %; 26 %) у 2009, 2014 та 2015 рр. Кращі, аніж по Україні в цілому (47,3 %; 60,6 %; 50,1 %; 57,4 %, 2012), показники визначаються типом поселення й географічним розміщенням. Виявлено також розбіжність в оцінках населенням України власного здоров’я (посереднє для 49,6 %) і системи охорони здоров’я в цілому (низька оцінка – три бали з десяти) станом на 2004 рік. The items of recreation and social health in Ukraine are actualized by the political and socioeconomic crisis and military operation in the Donbas. Having used the data of national and local monitoring which were achieved in accordance with the methodology for an integrated index of social well-being, and a downward dynamic of the cultural and recreational field benefit sufficiency was found out. Particularly, the inhabitants of Lutsk have experienced a deficiency in the capability to amuse their leisure completely (45,8 %; 19,2 %; 28,1 %); to have a good rest (54,8 %; 35,8 %; 42,9 %); to receive necessary medical care (40,5 %; 44,6 %; 45,9 %); and health deterioration (36,5 %; 22,2 %; 26 %) in 2009, 2014 and 2015 respectively. Proportional indexes for the city of Lutsk are some better than for Ukraine on the whole (47,3 %; 60,6 %; 50,1 %; 57,4% in 2012), which is explained by the type of settlement and geographical position. However, they (indexes) are taking a step for the worse after 2014. As part of the study, the differences in the assessment of their health by the population of Ukraine (49,6 % of the population assessed their health as underwhelming) and the standards of health care (low rating – score 3 of 10) were found out (2004).
The Condition of Cultural and Recreational Sphere and Social Health in the Perception of Ukraine’s Population and the Inhabitants of Lutsk
Keywords: соціальне самопочуття; культурно-рекреаційна сфера; соціальне здоров’я; місто Луцьк; social well-being; cultural and recreational sphere; social healthk; the city of Luts